2005
DOI: 10.1080/02687030444000723
|View full text |Cite
|
Sign up to set email alerts
|

Holistic assessment of narrative quality: A social validation study

Abstract: Background: There is a tradition of social validation studies in the adult clinical treatment literature that has not yet been extended to narrative evaluation. This social validation process begins with lay listener holistic judgements of narrative quality for non-brain-injured narrators, and compares these judgements to clinician-researchers' assessments of the same narratives. The resulting narratives rated for quality reflect the premorbid range of skills in clinical populations, and overall narrative perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Similarly, the use of a well-proven quality assessment form (Streit Olness et al, 2005) contributed to ensuring the social validity of the individual clinical statements. During the quality assessment and data analysis processes, the research team was conscious of the group's preunderstanding and made no assumptions without reviewing and analyzing the studies until consensus was reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the use of a well-proven quality assessment form (Streit Olness et al, 2005) contributed to ensuring the social validity of the individual clinical statements. During the quality assessment and data analysis processes, the research team was conscious of the group's preunderstanding and made no assumptions without reviewing and analyzing the studies until consensus was reached.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Streit Olness et al (2005), all articles were carefully read to assess the quality of the social validity of the individual clinical statements. Specifically, the focus was on evaluating researchers and clinicians' analytic and holistic assessment of the statements' quality, and overall, the characteristics of patient statements along a continuum of quality.…”
Section: Methodsmentioning
confidence: 99%
“…SS was a story from an older child and showed more complexity than WBB, as illustrated by more and longer utterances, more diverse vocabulary, and higher MISL scores. Previous research comparing ratings of narrative quality found agreement was highest at the ‘polar extremes’ of the rating scale (Streit Olness et al, 2005). It is possible that, since SS was a more complex and developed story, it was clearer for all raters, regardless of experience, to identify strengths and score consistently.…”
Section: Discussionmentioning
confidence: 93%